THE ADVICES TO LIFE: A PHILOLOGICAL STUDY OF THE NAZAM TEXT LIFE ADVICES - Nofrizal Nofrizal (Farabi, 2023)
Nazam is a Malay Islamic literary work which is an important means of delivering religious dakwah in Minangkabau. This research uses th uses the Nazam Life Advice Manuscript from Surau Parak Laweh, West Sumatra as the object and primary source of the research. This research raises the issue of the advice that must be done in living the life contained in the Nazam Naskah Advice on Life. In this regard, this study aims to describe the manuscript in terms of the condition of the manuscript, the presentation of the text edition and the disclosure of the contents of the text related to life advice that is relevant to this day. Through this research, the researcher discusses and explores the issue of life advice that is relevant to the current conditions based on a study of the main source of the Nazam Nazam Naskah Life Advice. Source reading is done using philological and hermeneutical approaches. The philological approach is used to describe the manuscript, presenting the edition of the text which is carried out using the critical edition method to produce a text that can be read by researchers and the general public. After getting the text edition, contextualization was carried out using a hermeneutic approach. Based on the reading results, it shows that there are three main pieces of advice contained in this Nazam Life Advice text. First, advice in protecting property and children. Second, advice to be sincere and stay away from riya. Third, advice to stay away from arrogant.